STRENGTHENING LOCAL INSTITUTIONS IN THE MANAGEMENT OF ADAT LAKES (BAKUOK LAKES) KAMPAR DISTRICT - Mimin Sundari Nasution; Zulkarnaini Zulkarnaini; Mayarni Mayarni (Sosiohumaniora, 2021)
A conservation area that has cultural-based fisheries activities, traditional leaders play a role as activity controllers and have a vision to conserve and provide protection in the area around this customary lake. On the other hand, ecologically, Bakuok Lake is very worrying. Based on the rules regarding the prohibition on Lake Bakuok, not all of these rules were carried out and implemented properly, even though there were already monitoring, there were still violations that occurred. The number of institutions involved in the development of Lake Bakuok have so far been temporary or temporary in nature, and have run separately and have not yet formed a systematic collaboration. This study aims to see how to strengthen local institutions in the sustainable management of Lake Bakuok. This research uses qualitative research methods that aim to obtain a holistic (holistic) picture of a phenomenon in Lake Bakuok. The results showed several important items that the institutional strengthening of lolak in the management of Danau Bakuok was not optimal. As seen from the dimension of human resource development that has not been maximized where there is no training or technical provisioning in order to increase skills. The dimension of organizational strengthening is also not optimal even though there is support for several activities but it is only temporary and unsustainable. Meanwhile, in the institutional reform dimension, it was found that several rules and regulations that had been made by ninik mamak were still violated.